2006
DOI: 10.1681/asn.2005040404
|View full text |Cite
|
Sign up to set email alerts
|

A Locus for Renal Malformations Including Vesico-Ureteric Reflux on Chromosome 13q33–34

Abstract: Congenital anomalies of kidney and urinary tract (CAKUT), including vesico-ureteric reflux (VUR), are major causes of ESRD in childhood. Herein is reported evidence for a locus on 13q33q34 associated with CAKUT. Deletion mapping of chromosome 13q was performed in four children with CAKUT using 31 microsatellite markers on peripheral blood genomic DNA that was obtained from the patients and their parents. mRNA expression of the positional candidate genes was compared with sequences in electronic databases in si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…We compared the clinical features of our patients with eight previously published patients with deletions of chromosome region 13q33-34 [Turleau et al, 1978;Mucke et al, 1983;Stoll and Alembik, 1998;Luquet et al, 1999;Luo et al, 2000;Vats et al, 2006;Ballarati et al, 2007] (Table I). Developmental delay/mental retardation, microcephaly, and facial dysmorphisms were present in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…We compared the clinical features of our patients with eight previously published patients with deletions of chromosome region 13q33-34 [Turleau et al, 1978;Mucke et al, 1983;Stoll and Alembik, 1998;Luquet et al, 1999;Luo et al, 2000;Vats et al, 2006;Ballarati et al, 2007] (Table I). Developmental delay/mental retardation, microcephaly, and facial dysmorphisms were present in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Data regarding linkage with regions identified in this study on chromosomes 2, 3, 4, 10, 13, 16 and 20 were supported by smaller linkage studies or studies of chromosomal rearrangements associated with vur, usually in association with other urinary tract malformations. 22,[127][128][129][130][131][132][133] For example, the second highest linkage peak in this study was in chromo some 10q26, with the linkage peak clearly distal to potential candidate genes FGFR2 and PAX2. a study of 10 patients with monosomy of 10q26 and urinary anomalies (such as vur and hypoplastic kidney) with or without genital anomalies provided evidence for a gene or genes involved in kidney development in the same region.…”
Section: N a T U R E R E V I E W S U N C O R R E C T E D P R O O Fmentioning
confidence: 59%
“…131 special attention should be drawn to the region on chromosome 13q32-q33, which was not the highest peak in the study by Kelly et al 47 but received support from two other linkage studies 22,127 and a study of chromo somal rearrangements. 132 it is particularly noteworthy that a genome-wide linkage scan for end-stage renal disease (esrD) 130 and a candidate gene association study for chronic kidney disease (CKD) 133 provide further data to support a role for this region in renal disease or CaKut. the esrD study also revealed evidence for linkage at 10q26, 1q25, 6q24 and 4p15.32, 130 all of which are close to or overlapping with regions identified by Kelly et al the CKD candidate gene study provided support for loci identified by Kelly et al at 6q24-q25, 16q24.3, and 20p11.2.…”
Section: N a T U R E R E V I E W S U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…Since animal studies now suggest a much larger role of RET in CAKUT, further investigations in larger human cohorts and in a broader urinary system development and have been found to be associated with mutations in patients with isolated kidney defects or in syndromes include BMP4, FOXC1, ACE, Chr13q33-34, GATA3, PAX2, EYA1, SAL1 and SIX1. [55][56][57][58] Animal studies have indicated that many of these influence Gdnf-Ret signaling. Recently, RET coding region mutations were identified in 12 between genes deemed important from animal studies and the identification of mutations in these in CAKUT.…”
Section: Genetics Of Cakutmentioning
confidence: 99%